Potensi Berwirausaha Mahasiswa Pendidikan Tata Boga Jurusan Ilmu Kesejahteraan Keluarga Universitas Negeri Padang - Nurhasanah, Nurhasanah; Yulastri, Asmar; Fridayati, Lucy (Journal of Home Economics and Tourism, 2016)
This research was motivated by the desire for entrepreneurship education student Catering is high, but in fact are not able to work as an entrepreneur. The purpose of this study was to describe the potential of entrepreneurship education student Catering Department of Family Welfare. This research is descriptive quantitative. The population in the study were all students of Education Catering Padang State University 2010-2012 forces numbering 83 people, and all of them sampled. The data collection technique for potential entrepreneurship using a questionnaire prepared by the "Likert Scale". Furthermore, the data were analyzed with the aid of a computer program SPSS version 18.00. The results showed that the overall potential of entrepreneurship students included into either category (76%). Descriptive analysis of data potential of entrepreneurship students perindikator note that the indicators of personality interpretation either by 77.75%, self-discipline interprestasi enough of 73.75%, the creativity of interpretation either by 75.25%, the urge / desire interpretation of either 77%, the courage to face the risk of interpretation fairly 71.75%, confidence interpretation of either 78%.Keywords: Potential, Entrepreneurship, Student Education Catering